2009
DOI: 10.1007/s11606-009-0945-5
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Controlled Trial of the Influence of a Geriatrics Home Visit Program on Medical Student Knowledge, Skills, and Attitudes Towards Care of the Elderly

Abstract: PURPOSE:To determine the impact of a geriatrics home visit program for third-year medical students on attitudes, skills, and knowledge.METHODS: Using a mixed methods, prospective, controlled trial, volunteer control group students (n=17) at two sites and intervention group students (n=16) at two different sites within the same internal medicine clerkship were given Internet and CDROM-based geriatric self-study materials. Intervention group students identified a geriatrics patient from their clinical experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 7 publications
(13 reference statements)
0
22
1
1
Order By: Relevance
“…Even interventions of relatively brief duration, for example, an electronic game, 38 a 1-week geriatrics course, 29 and a 3-hour falls and delirium prevention session with selfstudy, 39 demonstrated an immediate positive change in student knowledge. One study compared a didactic teaching intervention with a novel experiential teaching intervention; Locally developed Improvement in some aspects of attitude after intervention; better scores on some aspects of attitude in intervention than control Bernard et al 19 Cohort 294 1st-year students, United States Senior mentor program Intermittent over 2 years ASD Attitudes improved in both cohorts but more so in the intervention group Denton et al 26 Before-and-after intervention with control cohort 33 3rd-year student, United States…”
Section: Attitudesmentioning
confidence: 99%
“…Even interventions of relatively brief duration, for example, an electronic game, 38 a 1-week geriatrics course, 29 and a 3-hour falls and delirium prevention session with selfstudy, 39 demonstrated an immediate positive change in student knowledge. One study compared a didactic teaching intervention with a novel experiential teaching intervention; Locally developed Improvement in some aspects of attitude after intervention; better scores on some aspects of attitude in intervention than control Bernard et al 19 Cohort 294 1st-year students, United States Senior mentor program Intermittent over 2 years ASD Attitudes improved in both cohorts but more so in the intervention group Denton et al 26 Before-and-after intervention with control cohort 33 3rd-year student, United States…”
Section: Attitudesmentioning
confidence: 99%
“…For instance, Medina-Walpole et al found that respective experiences successfully enhanced the geriatric curricular content and positively affected students’ attitudes towards chronically ill and homebound elderly persons [23]. Furthermore, Denton et al described a positive effect, especially with regard to attitudes [24]. Our results indicate that undergraduate medical students need a structuring tool serving as interpretation aid to handle the complexity of a CGA.…”
Section: Discussionmentioning
confidence: 64%
“…If the quality of contact is high i.e. in-depth, then this may lead to improved attitudes, as shown by a trial among students visiting geriatric patients at home[36]. Furthermore, more long-term and frequent high quality contact seems to reduce prejudice[35].…”
Section: Discussionmentioning
confidence: 99%